COGNITIVE OUTCOMES ASSOCIATED WITH PHENYLALANINE, AN ESSENTIAL AMINO ACID, IN A MIDDLE-AGED SAMPLE. (16th November 2018) - Alwerdt, J; Sliwinski, M; Patterson, A
Abstract: Emerging evidence indicates metabolic perturbations may occur before signs of cognitive decline become evident. Therefore, early detection of metabolic markers may give the opportunity to intervene and prevent future neurodegenerative disorders. Given that phenylalanine (Phe) is an essential amino acid that regulates downstream processes entailing the blood-brain-barrier and neurological function, further research disentangling its role may be valuable. This study includes data from the Effects of Stress on Cognitive Aging, Physiology, and Emotion (ESCAPE) to examine the phenylalanine association with cognition. The sample consisted of 223 diverse, middle-aged adults (M = 47.39 years, SD = 10.88) that included both fasting serum samples measured by LC-MS/MS and data on all cognitive measures representing spatial memory, speed of processing (SOP), and working memory. Overall, the results demonstrate that higher levels of Phe were associated with worse SOP while controlling for age, gender, education, ethnicity, and BMI. Interestingly, none of the other cognitive measures were significant. Among cognitive domains, SOP is known to decline with age regardless of underlying cognitive dysfunction. Therefore, identifying risk factors for SOP can have broad implications for the population. Further research is needed to understand the underlying networks involved and other interconnections that may be occurring. These findings contribute to identifying potential metabolic targets to improve cognitive function and prevent cognitive decline.